Sex, Nativity, and Disability in Older Mexican Americans - Nam, Sanggon (J Am Geriatr Soc, 2015)
BACKGROUND/OBJECTIVES: Although older Mexican Americans are a rapidly growing segment of the U.S population, with high rates of disability, there is presently little research examining nativity and sex differences in activities of daily living (ADL) and mobility limitations in older Mexican Americans compared to general studies of the older population. This study examined the effect of nativity and sex on ADL and mobility limitations in older Mexican Americans. DESIGN, SETTING, PARTICIPANTS, MEASUREMENTS: 2,069 non-institutionalized Mexican American aged 75 years and older from the Hispanic Established Population for the Epidemiological Study of the Elderly (Hispanic EPESE) (2004-2005). Socio-demographics, self-reported medical conditions (arthritis, cancer, diabetes, stroke, heart attack, and hip fracture), ADLs, and gross mobility function were obtained. RESULTS: Out of 2069, 56.3% were US-born and 43.7% were Mexico-born. The prevalence of ADL and mobility limitation in both US-born and Mexico-born was 32.9% vs. 33.9% and 56.6% vs. 55.6%, respectively. Compared to US-born subjects, Mexico-born tend to report less ADL limitation (OR=0.79; CI: 0.59- 1.05) after controlling for socio-demographic variables and medical conditions. Similarly, they were less likely to report mobility limitation (OR=0.64; CI: 0.48- 0.86) after controlling for all covariates. There was a significant interaction effect between nativity and sex (OR=0.42; CI=0.24-0.74) on ADL limitation suggesting that Mexico-born men were less disabled than US-born while the opposite was true for women. No significant interaction between nativity and sex was found for mobility limitation. CONCLUSION: We found that Mexico-born men were less disabled than US-born counterparts. However, Mexico-born women were more likely to report disability than Mexico-born men.